Eksplorasi Nilai-Nilai Keuangan Berkelanjutan Dalam Praktik ESG (Environmental, Social, Governance): Studi Multi-Kasus Di Indonesia: Exploring Sustainable Finance Values in ESG (Environmental, Social, Governance) Practices: A Multi-Case Study in Indonesia - Prasetyono Hendriarto; Lukman Sangapan; Adler Haymans Manurung (Jurnal Bisnis dan Ekonomi, 2025)
This study aims to explore the values of sustainable finance within the practice of Environmental, Social, and Governance (ESG) through a multi-case study in Indonesia. The research focuses on how companies internalize ESG not merely as a regulatory obligation but also as a strategy to build competitiveness, reputation, and long-term sustainability. The research employed a qualitative approach with a multi-case study design, collecting data through in-depth interviews, sustainability report analysis, and official document reviews. Data were analyzed using thematic analysis techniques with triangulation to enhance the validity of the findings. The results indicate that ESG implementation in Indonesia remains diverse: while some companies have integrated ESG into their business strategies, others tend to engage in symbolic reporting (greenwashing). Strong ESG practices have been proven to generate positive impacts on sustainable financial value, including increased profitability, strengthened stakeholder relations, and more effective risk management. Furthermore, ESG implementation contributes significantly to society through social empowerment, environmentally friendly technological innovation, and the enhancement of sustainability literacy. The study concludes that ESG plays a pivotal role as the foundation of a sustainable financial system in Indonesia. These findings reinforce the argument that ESG practices are not merely compliance instruments but also essential drivers in creating long-term economic and social value.